To demonstrate polynomial addition correctly, we need to combine like terms properly.
Let's analyze each response:
-
First response: \((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 13x^2 + 9x + 10\)
This is incorrect because \(2x^2 + 3x^2\) should equal \(5x^2\), not \(13x^2\). -
Second response: \((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10\)
This is correct. We combine like terms:- \(2x^2 + 3x^2 = 5x^2\)
- \(6x + 3x = 9x\)
- \(1 + 9 = 10\)
-
Third response: \((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^4 + 9x^2 + 10\)
This is incorrect because there are no \(x^4\) terms in the original polynomials. -
Fourth response: \((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = -x^2 + 3x - 8\)
This is incorrect because the calculations do not properly add the terms.
The correct example demonstrating polynomial addition is the second response:
\((2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10\).